Vitamin K content of cheese, yoghurt and meat products in Australia - Dunlop, Eleanor; Jakobsen, J.; Jensen, M.B.; Arcot, J.; Qiao, L.; Cunningham, Judy; Black, Lucinda (ELSEVIER SCI LTD, 2022)
Vitamin K is vital for normal blood coagulation, and may influence bone, neurological and vascular health. Data on the vitamin K content of Australian foods are limited, preventing estimation of vitamin K intakes in the Australian population. We measured phylloquinone (PK) and menaquinone (MK) -4 to -10 in cheese, yoghurt and meat products (48 composite samples from 288 primary samples) by liquid chromatography with electrospray ionisation-tandem mass spectrometry. At least one K vitamer was found in every sample. The greatest mean (± standard deviation for foods sampled in multiple cities) concentrations of PK (4.9 µg/100 g), MK-4 (58 ± 9 µg/100 g) and MK-9 (8 ± 2 µg/100 g) were found in lamb liver, chicken leg meat and Cheddar cheese, respectively. Cheddar cheese (1.1 ± 0.3 µg/100 g) and cream cheese (1.0 µg/100 g) contained MK-5. MK-8 was found in Cheddar cheese only (4 ± 2 µg/100 g). As the K vitamer profile and concentrations appear to vary considerably by geographical location, Australia needs a vitamin K food composition dataset that is representative of foods consumed in Australia.